High efficiency electrochemical disinfection of Pseudomons putida using electrode of orange peel biochar with endogenous metals. (February 2022) - Sun, Wei; Lu, Zhili; Zuo, Kuichang; Xu, Shuo; Shi, Baoyou; Wang, Haibo
Abstract: The electrochemical disinfection efficiency of Pseudomons putida was studied using ruthenium iridium coated titanium (RICT) electrode as anode and carbonized orange peel biochar (OPB) or graphite as the cathode. The results indicated that RICT/OPB system induced 6.5 and 7.0 log of P. putia inactivation after 60 s at 2 V and 45 s at 10 V, respectively. RICT/OPB system showed better efficiency than RICT/graphite system. The energy consumption of OPB cathode (17.5 Wh m −3 per log) was significantly lower than that of graphite cathode (23.09 Wh m −3 per log). Both anode and cathode played great roles on the disinfection. The anode absorbed electric energy to generate electrical hole, which can oxidize chloride ions to chlorine free radicals. The continuous porous structure of OPB can provide more adsorption sites and reduce electrolyte transport resistance, resulting in more Cl· production. Moreover, P. putia was much easier adsorbed to the anode surface in the RICT/OPB system because of the stronger electrostatic repulsion between cells and OPB cathode. As a result, P. putia was more easily inactivated by the Cl· produced on the anode. Besides chlorine active species, superoxide radical (O2 ·﹣) produced on surface of cathode may also result in P. putia inactivation. The endogenous CuO in OPB can induce persistent free radicals (PFRs) production during pyrosis process. O2 ·﹣ can be produced by O2 activation through the function of Cu2 O/CuO and PFRs existed in OPB cathode. The more superoxide radical production led to the better disinfection effect than the graphite cathode. As a consequence, OPB electrode showed high efficiency electrochemical disinfection of P. putida . Graphical abstract: Image 1 Highlights: The electrode of orange peel biochar with endogenous metals was constructed. RICT/OPB system showed better disinfection efficiency than RICT/graphite system. The Cl· and O2 .- played great roles on the electrochemical disinfection of bacteria. The continuous porous structure of OPB resulted in more Cl· production. Cu2 O/CuO and persistent free radicals in OPB induced more O2 .- production.